2014
DOI: 10.1371/journal.pone.0095426
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Artefacts of the Human Back: Comparison of the Sagittal Curvature of the Spine Measured Using Skin Markers and an Open Upright MRI

Abstract: Soft tissue artefact affects the determination of skeletal kinematics. Thus, it is important to know the accuracy and limitations of kinematic parameters determined and modelled based on skin marker data. Here, the curvature angles, as well as the rotations of the lumbar and thoracic segments, of seven healthy subjects were determined in the sagittal plane using a skin marker set and compared to measurements taken in an open upright MRI scanner in order to understand the influence of soft tissue artefact at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 46 publications
3
66
1
Order By: Relevance
“…Previous research showed that these angles differ by about 20° [67]. This limits the direct comparison of the lumbar angles reported in the current study with other studies; however, it does not affect the results of our regression analyses since all participants were measured identically.…”
Section: Limitationscontrasting
confidence: 52%
“…Previous research showed that these angles differ by about 20° [67]. This limits the direct comparison of the lumbar angles reported in the current study with other studies; however, it does not affect the results of our regression analyses since all participants were measured identically.…”
Section: Limitationscontrasting
confidence: 52%
“…The accurate measurement of segment kinematics is challenging due to the complexity of the soft tissues moving relative to the underlying skeletal structures (Taylor et al 2005;Zemp et al 2014). As a result, motion capture varies from techniques using data extracted from simple videos, through retro-reflective markers attached to the subject's skin, to extensive measurement using e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The standing trial was used as a basis to compute the relative positions of the two segments. For the spine, a segmental [31] and curvature approach [31,35,36] was used, and the curvature angle [37] was calculated.…”
Section: Data Processing and Analysismentioning
confidence: 99%